Legal and ethical principles of informed consent to vaccination in Russia: the need to change approach - A. A. Baranov; N. I. Briko; L. S. Namazova-Baranova; M. V. Fedoseenko (Педиатрическая фармакология, 2016)
The article analyzes the international experience in the regulation of procedures for obtaining voluntary informed consent to immunization as well as voluntary refusal of it. The authors set up the necessity of changing the approach to certain aspects of the obtaining voluntary consent to vaccination or refusal of it procedure regulation in the Russian Federation.